2007
DOI: 10.1182/blood-2007-05-091256
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetylation at the human β-globin locus changes with developmental age

Abstract: To delineate the relationship between epigenetic modifications and hemoglobin switching, we compared the pattern of histone acetylation and pol II binding across the ␤-globin locus at fetal and adult stages of human development. To make this comparison possible, we introduced an external control into experimental samples in chromatin immunoprecipitation (ChIP) assays. Using this common standard, we found that the locus control region (LCR) was acetylated to the same level at all stages, whereas acetylation lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 41 publications
(53 reference statements)
1
35
0
Order By: Relevance
“…In the active genes, the promoters were less acetylated compared with the coding regions. Finally, the level of acetylation per histone at the active γ and β promoters was clearly higher than that at the inactive ɛ promoter [44].…”
Section: Regulation Of γ-Globin Gene Expressionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the active genes, the promoters were less acetylated compared with the coding regions. Finally, the level of acetylation per histone at the active γ and β promoters was clearly higher than that at the inactive ɛ promoter [44].…”
Section: Regulation Of γ-Globin Gene Expressionmentioning
confidence: 85%
“…Only recently, the histone acetylation of the genes present at the level of the β-globin locus was explored in primary erythroblasts corresponding at various ontogenic stages (fetal vs. adult stage). This analysis showed that the LCR was acetylated to the same level at all stages, whereas acetylation levels at the individual gene regions correlated with the state of transcription [44]. In the active genes, the promoters were less acetylated compared with the coding regions.…”
Section: Regulation Of γ-Globin Gene Expressionmentioning
confidence: 92%
See 1 more Smart Citation
“…C) Diagram of the β-globin locus on chromosome 11 and acetylation status of H3 (top panel) and H4 (middle panel) and polymerase II (pol II, bottom panel) recruitment at the promoter region of the ε, γ and β globin genes in cells expressing high (fetal erythroblasts or adult erythroblasts treated with butyrric acid, white columns) or low (adult cells, grey column) levels of HbF. Acetylation of both H3 and H4 and binding of the pol II complex is relatively higher at the γ or β locus in cells expressing high or low levels of HbF, respectively (modified from Aerbajinai, Zhu, Gao, Chin, & Rodgers, 2007;Yin et al, 2007;Fathallah, Weinberg, Galperin, Sutton, & Atweh, 2007). Table 1 A) Induction of apoptosis in the myeloid leukaemia U937 cell line (white bars) and normal erythroid cells (grey bars) of compound 9, 11 and 24.…”
Section: Figure 1 Models Of the Mechanisms Of Reactivation Of Hbf Exmentioning
confidence: 99%
“…They are thought to act through epigenetic mechanisms since a durable association exists between epigenetic change and the developmental shape of globin gene expression. [61][62][63] The combined administration of recombinant EPO together with cytotoxic drugs has also been found to be beneficial for patients with low baseline EPO levels.…”
Section: Gamma-globulin Inducersmentioning
confidence: 99%